2014
DOI: 10.5194/acp-14-4185-2014
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft measurements of polar organic tracer compounds in tropospheric particles (PM<sub>10</sub>) over central China

Abstract: Abstract. Atmospheric aerosol samples were collected by aircraft at low to middle altitudes (0.8-3.5 km a.g.l.) over central East to West China during summer 2003 and spring 2004. The samples were analyzed for polar organic compounds using a technique of solvent extraction/BSTFA derivatization/gas chromatography-mass spectrometry. Biogenic secondary organic aerosol (SOA) tracers from the oxidation of isoprene were found to be more abundant in summer (3.3-138 ng m −3 , mean 39 ng m −3 ) than in spring (3.2-42 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 82 publications
(101 reference statements)
3
19
3
Order By: Relevance
“…SOA PIN exhibited the lowest concentration in the FT-WES (1.2 ng m −3 ) with a predominance of cis-pinonic acid (Table 2). Aircraft measurements in the FT over central China (Fu et al, 2014) recorded higher concentrations of 3-HGA (8.5 ng m −3 ) and MBTCA (1.9 ng m −3 ) than those measured in the present study (Table 2). Further-generation oxidation products (3-HGA and MBTCA) were higher in the BL (0.51 and 0.24 ng m −3 correspondingly; Table 2), with a statistically significant correlation (r = 0.90, p < 0.01) pointing to a same precursor.…”
Section: Tracers Of α-Pinene Oxidation (Soa Pin)contrasting
confidence: 49%
See 2 more Smart Citations
“…SOA PIN exhibited the lowest concentration in the FT-WES (1.2 ng m −3 ) with a predominance of cis-pinonic acid (Table 2). Aircraft measurements in the FT over central China (Fu et al, 2014) recorded higher concentrations of 3-HGA (8.5 ng m −3 ) and MBTCA (1.9 ng m −3 ) than those measured in the present study (Table 2). Further-generation oxidation products (3-HGA and MBTCA) were higher in the BL (0.51 and 0.24 ng m −3 correspondingly; Table 2), with a statistically significant correlation (r = 0.90, p < 0.01) pointing to a same precursor.…”
Section: Tracers Of α-Pinene Oxidation (Soa Pin)contrasting
confidence: 49%
“…Secondary products of isoprene oxidation (SOA ISO) evaluated in the present study are 2-methylglyceric acid (2-MGA), 2-methylthreitol (2-MT1) and 2-methylerythritol (2-MT2) (Claeys et al, 2004;Hallquist et al, 2009). Analogous FT concentrations of 2-methylthreitol and 2-methylerythritol were measured in the present study under the SAL (7.3 and 16.8 ng m −3 ; Table 2) and over the central China FT (8 and 17 ng m −3 ; Fu et al, 2014), one of the most important source regions of isoprene emission in the world during summertime (Guenther et al, 1995). Similar SOA ISO concentrations were found in the BL within the SAL and the WES (∼ 17 and ∼ 16 ng m −3 respectively) revealing the emission and subsequent ascending transport of biogenic or anthropogenic compounds, as found in previous studies performed at Izaña, which observed emissions of isoprene during daytime associated with anthropogenic compounds (Salisbury et al, 2006).…”
Section: Tracers Of Isoprene Oxidation (Soa Iso)mentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to highly practical field measurements 152 and atmospheric sampling, 153 future research will continue to focus on deconstructing complex systems into their fundamental components and investigating real-time changes to organic surfaces during exposure to a controlled flux of gas-phase oxidants.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The daily limits are exceeded mainly in winter due to increased traffic, domestic heating, industrial processes and meteorological phenomena such as inversion or low wind speed. [1][2][3][4][5] Airborne suspended particulate matter can be of natural (forests, pollen, rainfall, storm, vegetation, volcanic ash...) or anthropogenic origin (emissions of industry, transport, burning of fossil fuels, biomass, agriculture...). Primary particles are released into the atmosphere from sources on the Earth's surface.…”
Section: Introductionmentioning
confidence: 99%